Neutrophils in cancer: At the crucial crossroads of anti‐tumor and pro‐tumor - Wenpeng Cai; Tao Fan; Chu Xiao; Ziqin Deng; Yixiao Liu; Chunxiang Li; Jie He (Cancer Communications)
Abstract Neutrophils are important components of the immune system and play a key role in defending against pathogenic infections and responding to inflammatory cues, including cancer. Their dysregulation indicates potential disease risk factors. However, their functional importance in disease progression has often been underestimated due to their short half‐life, especially as there is limited information on the role of intratumoral neutrophils. Recent studies on their prominent role in cancer have led to a paradigm shift in our understanding of the functional diversity of neutrophils. These studies highlight that neutrophils have emerged as key components of the tumor microenvironment, where they can play a dual role in promoting and suppressing cancer. Moreover, several approaches to therapeutically target neutrophils have emerged, and clinical trials are investigating their efficacy. In this review, we discussed the involvement of neutrophils in cancer initiation and progression. We summarized recent advances in therapeutic strategies targeting neutrophils and, most importantly, suggested future research directions that could facilitate the manipulation of neutrophils for therapeutic purposes in cancer patients.